2022
DOI: 10.1111/1475-6773.14022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health care strikes on patient mortality: A systematic review and meta‐analysis of observational studies

Abstract: Objective: This study sought to evaluate the impact of health care strike action on patient mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
2
19
0
1
Order By: Relevance
“…This review also sits alongside at least three recent systemic and scoping reviews that explore strike action. Two of these studies examined the impact of strike action on patient outcomes, notably mortality and a range of other patient outcomes (such as hypertension control and chlamydia rates; Essex, Milligan, et al, 2022; Essex, Weldon, et al, 2022). Notably, while each review notes a number of limitations in regard to the literatre, it was found that strike action did not result in an increase in patient mortality and did not negatively impact a range of other patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review also sits alongside at least three recent systemic and scoping reviews that explore strike action. Two of these studies examined the impact of strike action on patient outcomes, notably mortality and a range of other patient outcomes (such as hypertension control and chlamydia rates; Essex, Milligan, et al, 2022; Essex, Weldon, et al, 2022). Notably, while each review notes a number of limitations in regard to the literatre, it was found that strike action did not result in an increase in patient mortality and did not negatively impact a range of other patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This search strategy has been published and applied elsewhere (Essex, Weldon, et al, 2022) The following databases were searched: EMBASE (1980–2021), MEDLINE (1946–2021), CINAHL (1982–2001), BIOETHICSLINE (1972–1999), EconLit (1969–2021), WEB OF SCIENCE (1960–2021). In addition, grey literature was searched through OPEN GREY and SIGMA REPOSITORY.…”
Section: Methodsmentioning
confidence: 99%
“…A 2022 systematic review and meta-analysis of observational studies compared patient mortality during a healthcare worker strike with that before or after the strike. Across more than 1.8 million admissions or presentations to care, in the aggregate, there were no clear negative effects of strike action on patient mortality 16. However, studies included in the systematic review were highly variable in quality and setting, and several studies included in the meta-analysis suggested the possibility of patient harm from strikes.…”
Section: Are Patients Harmed By Strikes?mentioning
confidence: 99%
“…The analysis by Essex et al 1 in this issue is a thorough and much‐needed review of physician strikes across numerous countries. It addresses an important question regarding the wisdom of extending labor law to physicians: whether allowing physicians to strike would lead to undesirable public health consequences.…”
Section: Introductionmentioning
confidence: 99%